Sintesis Barium Heksaferrit Tipe W Melalui Metode Mechanical alloying - Desriyan Lestari; Widyaningrum Indrasari; Erfan Handoko (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
W-type Barium hexaferrite with a crystal structure BaMe2Fe16O27 (Me is a divalent metal) has a good magnetic properties and high value of currie temperature. Ion substitution on W-type Barium Hexaferrite can be improve the properties of W-type Barium Hexaferrite. For this research, substitution Fe by ion Co and Ti with x = 0 and 0.1 by mechanical alloying method will be performed. Mixing of basic materials BaCO3, Fe2O3, Co3O4, and TiO2 by milling process using high energy ball mill in a wet milling condition using toluene for 1 hour followed with calcination and sintering. Then Crystal structure in the sample will be analyzed using XRD (X-Ray Diffraction) with CuKα radiation. The calculation of the phase BaCoTiFe16O27 (x = 0) obtained values of lattice parameters a=b= 5.886 Å dan c= 23.236 Å, while the phase BaCoTiFe15.8Co0.1Ti0.1O27 (x = 0.1) obtained values of lattice parameters a=b= 5.894 Å dan c= 23.257 Å. Keywords: W-type Barium Hexaferrite, Mechanical Alloying, X-Ray Diffraction, Lattice Parameter, Grain Size, Volume Unit Cell.